Differences in p53 status significantly influence the cellular response and cell survival to 1,25-dihydroxyvitamin D3-metformin cotreatment in colorectal cancer cells - Abu El Maaty, Mohamed A.; Strassburger, Wendy; Qaiser, Tooba; Dabiri, Yasamin; Wölfl, Stefan (Molecular carcinogenesis, 2017)
Mutations in the tumor suppressor p53 are highly prevalent in cancers and are known to influence the sensitivity of cells to various chemotherapeutics including the anti-cancer candidates 1,25-dihydrovitamin D3 [1,25D3] and metformin. Previous studies have demonstrated additive/synergistic anti-cancer effects of the 1,25D3-metformin combination in different models, however, the influence of p53 status on the efficacy of this regimen has not been investigated. The CRC colorectal cancer (CRC) cell lines HCT116 wild-type (wt), HCT116 p53−/−, and HT-29 (mutant; R273H) were employed, covering three different p53 variations. Synergistic effects of the combination were confirmed in all cell lines using MTT assay. Detailed evaluation of the combination's effects was performed, including on-line measurements of cellular metabolism (glycolysis/respiration) using a biosensor chip system, analyses of mitochondrial activity (membrane potential and ATP/ROS production), mRNA expression analysis of WNT/β-catenin pathway players, and a comprehensive proteomic screen using immunoblotting and ELISA microarrays. AMPK signaling was found to be more strongly induced in response to all treatments in HCT116 wt cells compared to other cell lines, an observation that was coupled to a stronger accumulation of intracellular ROS in response to metformin/combination, and finally an induction in autophagy, depicted by an increase in LC3II:LC3I ratio in combination-treated cells compared to mono-treatments. An induction in apoptotic signaling was observed in the other cell lines in response to the combination, illustrated by a decrease in expression of pro-survival Bcl2 family members. P53 status impacts cellular responses to the combination but does not hamper its anti-proliferative synergy.
Gesehen am 26.09.2018